2008
DOI: 10.1038/ng.150
|View full text |Cite
|
Sign up to set email alerts
|

De novo mutations in the gene encoding STXBP1 (MUNC18-1) cause early infantile epileptic encephalopathy

Abstract: Early infantile epileptic encephalopathy with suppression-burst (EIEE), also known as Ohtahara syndrome, is one of the most severe and earliest forms of epilepsy. Using array-based comparative genomic hybridization, we found a de novo 2.0-Mb microdeletion at 9q33.3-q34.11 in a girl with EIEE. Mutation analysis of candidate genes mapped to the deletion revealed that four unrelated individuals with EIEE had heterozygous missense mutations in the gene encoding syntaxin binding protein 1 (STXBP1). STXBP1 (also kno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

21
458
1
7

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
3

Relationship

4
6

Authors

Journals

citations
Cited by 496 publications
(496 citation statements)
references
References 29 publications
21
458
1
7
Order By: Relevance
“…All the variants were confirmed as de novo by Sanger sequencing, and were predicted to be damaging by Web‐based prediction tools, and not found in ExAC (http://exac.broadinstitute.org) and gnomAD database (http://gnomad.broadinstitute.org/) (Table S1). Parentage was confirmed by microsatellite analysis as previously described 24. We confirmed that c.817‐1G>A causes skipping of exon 11 leading to in‐frame deletion (p.His273_Lys300del) and other two minor abnormal splicing resulting in frameshift using minigene assay (Fig.…”
Section: Resultssupporting
confidence: 71%
“…All the variants were confirmed as de novo by Sanger sequencing, and were predicted to be damaging by Web‐based prediction tools, and not found in ExAC (http://exac.broadinstitute.org) and gnomAD database (http://gnomad.broadinstitute.org/) (Table S1). Parentage was confirmed by microsatellite analysis as previously described 24. We confirmed that c.817‐1G>A causes skipping of exon 11 leading to in‐frame deletion (p.His273_Lys300del) and other two minor abnormal splicing resulting in frameshift using minigene assay (Fig.…”
Section: Resultssupporting
confidence: 71%
“…These include mutations in syntaxin‐1B (STX1B), SNAP‐25, and syntaxin binding protein 1 (STXBP1/Munc 18‐1) (Rohena et al., 2013; Saitsu, Kato, Mizuguchi, Hamada, & Osaka, 2008; Schubert, Siekierska, Langlois, May, & Huneau, 2014). The current study of kindling facilitation in a viable STXBP5/tomosyn‐1‐deficient mouse suggests another potential synaptopathy that has not been described in humans.…”
Section: Discussionmentioning
confidence: 99%
“…8 Biological parentage was judged if more than four informative markers were compatible and other uninformative markers showed no discrepancies.…”
Section: Parentage Testingmentioning
confidence: 99%